2022
DOI: 10.1002/ejp.1991
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic‐like pain symptoms in inflammatory hand osteoarthritis lower quality of life and may not decrease under prednisolone treatment

Abstract: Background: Pain is common in hand osteoarthritis (OA) and multiple types may occur. We investigated the prevalence, associated patient characteristics, influence on health-related quality of life (HR-QoL) and response to antiinflammatory treatment of neuropathic-like pain in inflammatory hand OA. Methods: Data were analysed from a 6-week, randomized, double-blind, placebocontrolled trial investigating prednisolone treatment in 92 patients with painful inflammatory hand OA. Neuropathic-like pain was measured w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 40 publications
2
9
1
Order By: Relevance
“…A previous study used the DN4 questionnaire and found that 42% of patients with hand OA experienced NP [9], in line with our own findings using the same questionnaire. Another study previously used the PainDETECT questionnaire and reported an NP frequency of 19% in patients with hand OA [10], which is lower than that observed in our study (32.4%) using this questionnaire. Petterson et al found a prevalence of 42% for central sensitization measured with temporal summation tests in patients with hand OA [27].…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…A previous study used the DN4 questionnaire and found that 42% of patients with hand OA experienced NP [9], in line with our own findings using the same questionnaire. Another study previously used the PainDETECT questionnaire and reported an NP frequency of 19% in patients with hand OA [10], which is lower than that observed in our study (32.4%) using this questionnaire. Petterson et al found a prevalence of 42% for central sensitization measured with temporal summation tests in patients with hand OA [27].…”
Section: Discussioncontrasting
confidence: 97%
“…In subjects affected by knee OA, NP correlates with the severity of symptoms, joint function, psychological well-being, and the intake of painkillers [ 7 , 8 ]. Although understudied, it has been reported that NP may occur in 16–42% of patients with hand OA using different assessment questionnaires [ 9 , 10 ]. In the Magni N et al cohort of 121 patients with symptomatic hand OA, the prevalence of NP was estimated at 42% using the Douleur Neuropathique en 4 Questions (DN4) questionnaire [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may in part be explained by the greater number of joints involved, the longer duration of the disease, and presence of higher neuropathic-like pain in those with both the CMC and IP pain. The potential effect of neuropathic-like pain is supported by our findings of a lower prevalence of moderate to severe radiological (KL grade 3–4) and higher neuropathic-like pain in participants with both the and IP pain, which is similar to previous findings [ 10 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, our results suggest that neuropathic-like pain may be especially important in those with pain at more than one site, irrespective of the degree of joint damage which is supported by previous data [ 24 , 25 ]. The presence of neuropathic-like pain may reduce the efficacy of other therapies in OA [ 23 ]. This needs to be considered when developing treatment strategies for patients and consideration should be given to target neuropathic-like pain when present.…”
Section: Discussionmentioning
confidence: 99%